2011
DOI: 10.1186/1475-2891-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Rye kernel breakfast increases satiety in the afternoon - an effect of food structure

Abstract: BackgroundThe structure of whole grain cereals is maintained to varying degrees during processing and preparation of foods. Food structure can influence metabolism, including perceived hunger and satiety. A diet that enhances satiety per calorie may help to prevent excessive calorie intake. The objective of this work was to compare subjective appetite ratings after consumption of intact and milled rye kernels.MethodsTwo studies were performed using a randomized, cross-over design. Ratings for appetite (hunger,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 31 publications
2
36
1
Order By: Relevance
“…We speculate that the less consistent results in Study one compared with Study two were due to a too high over-all breakfast intake and/or energy intake which masks differences between tested breads due to the fact that participants reported high satiety ratings for both diets. This is to some degree supported by results from previous studies [15,16]. However, the macronutrient composition differed slightly between our our two studies and that could also have affected the results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We speculate that the less consistent results in Study one compared with Study two were due to a too high over-all breakfast intake and/or energy intake which masks differences between tested breads due to the fact that participants reported high satiety ratings for both diets. This is to some degree supported by results from previous studies [15,16]. However, the macronutrient composition differed slightly between our our two studies and that could also have affected the results.…”
Section: Discussionsupporting
confidence: 91%
“…These studies have included breads and porridges based on intact or milled rye fractions, representing large differences in food structure, which is known to affect metabolism, glycemic index and satiety [16]. However, so far no study has investigated the effect of whole grain rye crisp bread, which is an important contributor to whole grain rye intake in Sweden [22].…”
Section: Introductionmentioning
confidence: 99%
“…Other small experimental studies have found that omitting breakfast and the composition of breakfast have effects on appetite and metabolic parameters that could impact long-term metabolic risk (3537). Further trials have demonstrated that the content of breakfast is likely important for lower metabolic risk as breakfast meals emphasizing low-glycemic whole grains had beneficial effects on appetite and metabolic parameters throughout the day (36,3840). The sensitivity analysis we performed examining different breakfast-type foods aligns with this point.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation suggests that the triticale cereal could possess beneficial appetite regulating properties. Based on recent and our studies we might further hypothesise that a whole grain triticale cereal breakfast slows down acute insulin response, it might reduce depression of blood glucose below baseline levels (reactive hypoglycaemia) in the late postprandial phase and possibly has lower energy intake at subsequent meals compared to commercial grain breakfast with high II (Nilsson et al, 2008;Isaksson et al, 2011;Peters et al, 2011). There is some evidence that glucose kinetics affects this process little and that particularly the secretion of insulin in response to food intake, induces satiety (Flint et al, 2007;Blaak et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…The effect on appetite and metabolic responses from whole grain rye and probably also whole grain triticale is most likely mediated by the large content of dietary fibre, but may also be due to bioactive compounds present in the kernel and other structures of grain (Isaksson et al, 2011;Rosén et al, 2011). Whatever the mechanisms involved, a lower postprandial plasma insulin response promotes a beneficial effect on human health outcomes (Blaak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%